Pengaruh Harga, Promosi dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada PT Batam Cipta Industri - Wati; Syaifullah (LPPM Universitas Putera Batam, 2022)
The rapid industrial development of Batam city has increased the basic human need for shelter. Buying property in the form of real estate or a home is also one of the best ways for many people to invest their money. This study aims to determine the influence of price, promotion and service quality on purchasing decision. The sample used in this study is 134 respondents using a proaility sampling technique. The data processing process uses descriptive analysis and multiple linear regression analysis. The results show that all research data are valid and reliable. From the results of the t-test we know that value (X1) promotion (X2) service quality (X3) > t table 1.978 with a significance <0.05. The f value shows calculated F > Ftable 2.69 and significance < 0.05, so it can be concluded that all independent variables are significant explanatory variables to the dependent